Comprehensive characterization of differentially expressed genes in thyroid cancer. (October 2017) - Wang, Jian; Chi, Shumei; Huang, Zhongke; Ye, Xiaojuan; Shi, Guohua; Chen, Dongfang; Lou, Cen
Aim: To explore the patterns of gene expression and functionally characterize the differentially expressed genes (DEGs) in thyroid cancer.Methods: DEGs were determined between 57 paired thyroid cancer and noncancerous tissues using DESeq2. Subsequently, the main functions of the DEGs were studied by a variety of analyses.Results: We identified a cohort of 752 upregulated and 309 downregulated DEGs in thyroid cancer. Several hub DEGs were found in the protein–protein interaction networks. We also revealed a set of DEGs that were dysmethylated, involved in copy number variations and associated with clinical features in thyroid cancer.Conclusion: These results provide some novel findings on DEGs in thyroid cancer, which will be useful to guide further investigation and target therapy for this disease.